2021
DOI: 10.12968/live.2021.26.s3.3
|View full text |Cite
|
Sign up to set email alerts
|

Sheep abortion – a roundtable discussion

Abstract: Foreword Abortion takes a heavy toll on the sheep industry, not only economically, but in emotional terms too. Enzootic abortion in ewes is consistently the most frequent diagnosis followed in descending order by infection with Toxoplasma gondii, Campylobacter spp., Salmonella spp. and Listeria spp. Causes of abortion also lead to increased barren rates, and the birth of weak lambs, so the impact of these pathogens is greater than just abortion. Fortunately there are vaccines for the two most common causes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The detected rate is less than the rate that recorded in Iran which is 50.6% (10).In the current study, the difference between infection recoded in compare with other study may due to geographic differences in the study area, seasonal of the study, techniques used in diagnosis, clinical signs management and control programs (11).The current study showed that high relationship between Campylobacter infection and placenta retention, that's due to the ability of Campylobacter to cause placentitis and the cotyledons separate easily from the caruncles. In addition, the placentitis lead to fibroblast activation which produce fibrin that leads to the attachment of placenta on uterus (12,13).The present study showed that 75% of abortion cases diagnosis as campylobacter infection were suffering from recurrent abortion, that's may due to other causes of previous abortion such as Brucella, Salmonella, Toxoplasma and non-infection causes or due to expos to high dosage of bacteria by contact with aborted fetus, placenta, and uterine discharges (14,15).Campylobacter spp. are common abortion causes in ewes, most abortion cases occur at the twelfth week of pregnancy and after 7-25 days after infection (17).…”
Section: Discussionmentioning
confidence: 64%
“…The detected rate is less than the rate that recorded in Iran which is 50.6% (10).In the current study, the difference between infection recoded in compare with other study may due to geographic differences in the study area, seasonal of the study, techniques used in diagnosis, clinical signs management and control programs (11).The current study showed that high relationship between Campylobacter infection and placenta retention, that's due to the ability of Campylobacter to cause placentitis and the cotyledons separate easily from the caruncles. In addition, the placentitis lead to fibroblast activation which produce fibrin that leads to the attachment of placenta on uterus (12,13).The present study showed that 75% of abortion cases diagnosis as campylobacter infection were suffering from recurrent abortion, that's may due to other causes of previous abortion such as Brucella, Salmonella, Toxoplasma and non-infection causes or due to expos to high dosage of bacteria by contact with aborted fetus, placenta, and uterine discharges (14,15).Campylobacter spp. are common abortion causes in ewes, most abortion cases occur at the twelfth week of pregnancy and after 7-25 days after infection (17).…”
Section: Discussionmentioning
confidence: 64%
“…This rate has remained constant over time, with only 596 cases of ovine abortion diagnoses being attributed to Listeria spp. in the United Kingdom between 2002 -2019 [69].…”
Section: Aaem Annals Of Agricultural and Environmental Medicinementioning
confidence: 99%